Development and characterisation of bacteria as a potential application in enduring the mechanical and durability characteristic of cement composite. (31st October 2022) - Kishore, Kamal; Gupta, Nakul; Saxena, Kuldeep Kumar; Lade, Jayahari
ABSTRACT: The current research focuses on the biomineralization in cement composite by Bacillus sphaericus and Escherichia coli bacteria. The Escherichia coli ( E. coli ) was isolated from the soil beneath the leaked sewage pipe. Harvesting the E. coli bacteria required isolation, growth, cultivation and characterisation. Furthermore, the potential of micro-organisms was checked on the mechanical properties of the cement composite and durability properties such as water absorption, rapid chloride permeability test (RCPT), and ultrasonic pulse velocity on 7- and 28-day curing period respectively. The bacterial cell concentration of 10 6, 10 7 and 10 8 cells/ml were chosen and mixed during concrete manufacturing. The results revealed that the mechanical properties of the concrete prepared from micro-cultures exhibiting improvements over strength. CNT-EC8 was showing 18.73% (39.3 N/mm 2 ) and 13.08% higher compressive and split tensile strength during 28 days respectively. Despite this, they also show 33.07% and 45.14% lesser charge passage rate in RCPT test respectively. The bacterium was shown to be capable of producing calcite precipitation, filling the micro pores and improving the cement composite's durability. As a result, using microbially generated crystal in concrete can be a useful strategy for lowering permeability and developing long-lasting concrete.